Temperature-dependent distribution of silver nano particles on ferroelectric substrate: Molecular dynamics simulation. (27th July 2018) - Liu, Yue; Tang, Jiaxi; Li, Jiuyang; Fu, Kai; Zhu, Haonan
Abstract: Silver nano particles have been widely used as catalyst for chemical industry. However, the catalytic efficiency of the silver has been limited by the aggregation of the silver, as the active sites are only located on the surface of the catalyst particles. In this paper we report the surface aggregation dynamics of silver on different ferroelectric polarization surface and temperature dependent behaviors. Meanwhile, reducing the particle size to obtain the dispersed morphology of silver was discussed by the dissipative particle dynamics method and density functional theory. The surface with upward polarization provides more electrons to the silver, which is responsible for the dispersed morphology of the silver.